Family and social experiences in children and adolescents with cancer expressed through their drawings - Olimpia Petzold; Darius Razavi (Universidad de Ciencias Médicas de La Habana, 2024)
Introduction: Assessing the family and social dimensions from the pediatric cancer patient's perspective encounters challenges, as children and adolescents often do not verbally express their needs and experiences related to family and interactions with others. Drawing emerges as a valuable method for psychological evaluation, offering access to the inner world of patients in an enjoyable and non-threatening manner.  Objective: To assess the family and social experiences of children and adolescents with cancer. Material and Methods: A qualitative research design with inductive content analysis was utilized. The study included twenty children aged 6-17 years diagnosed with cancer from the Hospital de Especialidades Pediátricas in Maracaibo, Venezuela. Data collection involved drawings, observations, and interviews conducted over three individual sessions. Results: Two main categories emerged from the analysis: (1) Family Dimension, encompassing aspects of the family dynamics from the patient's perspective, the patient's needs within the family context, significant figures for the patient, and the patient's perception of parental concerns; and (2) Social Dimension, which covers patients' appreciation for healthcare professionals and their social needs, such as the desire to be with friends, resume everyday life, and achieve goals in life. Conclusions: Drawing is a valid and effective tool for evaluating family and social interactions and needs in children and adolescents with cancer.